Complete Histological Resolution of Collagenous Sprue - Hugh J Freeman; Jennifer E Davis; Danny M Myers (Canadian Journal of Gastroenterology)
A 65-year-old woman developed a watery diarrhea syndrome with collagenous colitis. Later, weight loss and hypoalbuminemia were documented. This prompted small bowel biopsies that showed pathological changes of collagenous sprue. An apparent treatment response to a gluten-free diet and prednisone resulted in reduced diarrhea, weight gain and normalization of serum albumin. Later repeated biopsies from multiple small and large bowel sites over a period of over three years, however, showed reversion to normal small intestinal mucosa but persistent collagenous colitis. These results indicate that collagenous inflammatory disease may be a far more extensive process in the gastrointestinal tract than is currently appreciated. Moreover, collagenous colitis may be a clinical signal that occult small intestinal disease is present. Finally, collagenous sprue may, in some instances, be a completely reversible small intestinal disorder.